Criminal Liability of the Worker for Disclosing Professional Secrets - Farman, Abbas (Journal of Legal Sciences, 2025)
Maintaining secrets reflects the extent of trust placed by the owner of the secret in those with whom it was deposited, and revealing these secrets is considered one of the abhorrent and disgraceful acts that make their owner an object of contempt, ridicule, disrespect, and untrustworthy by others, and from this standpoint, in order to preserve the professional secrets of the employer (The legislator has obligated the worker to preserve these secrets that come to his knowledge by virtue of his profession and work, and aware of the danger of this act on the personal rights of the employer, in addition to its danger to the commercial business, and that it would expose the employer to serious harm. Therefore, the legislator criminalized this behavior. Representing the disclosure of professional secrets because of their significant impact and damage on the employer and on businesses and commercial projects in the future.